Development of a physiologically‐based pharmacokinetic model to simulate the pharmacokinetics of intramuscular antiretroviral drugs - Sara Bettonte; Mattia Berton; Manuel Battegay; Felix Stader; Catia Marzolini (CPT: Pharmacometrics & Systems Pharmacology)
Abstract There is growing interest in the use of long‐acting (LA) injectable drugs to improve treatment adherence. However, their long elimination half‐life complicates the conduct of clinical trials. Physiologically‐based pharmacokinetic (PBPK) modeling is a mathematical tool that allows to simulate unknown clinical scenarios for LA formulations. Thus, this work aimed to develop and verify a mechanistic intramuscular PBPK model. The framework describing the release of a LA drug from the depot was developed by including both the physiology of the injection site and the physicochemical properties of the drug. The framework was coded in Matlab® 2020a and implemented in our existing PBPK model for the verification step using clinical data for LA cabotegravir, rilpivirine, and paliperidone. The model was considered verified when the simulations were within twofold of observed data. Furthermore, a local sensitivity analysis was conducted to assess the impact of various factors relevant for the drug release from the depot on pharmacokinetics. The PBPK model was successfully verified since all predictions were within twofold of observed clinical data. Peak concentration, area under the concentration‐time curve, and trough concentration were sensitive to media viscosity, drug solubility, drug density, and diffusion layer thickness. Additionally, inflammation was shown to impact the drug release from the depot. The developed framework correctly described the release and the drug disposition of LA formulations upon intramuscular administration. It can be implemented in PBPK models to address pharmacological questions related to the use of LA formulations.